Postpartum evaluation of the role of maternal characteristics and mode of delivery on maternal attachment, anxiety and depression; a study conducted in Turkey’ : Maternal Anxiety and Depression Parameters in Turkey - Topbas Selcuki, Nura Fitnat; Yalcin Bahat, Pinar; Turan, Gokce; Aksoy, Umut; Bagci, Kubra; Ozdemir, Ismail (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The primary aim of this study was to compare mother-infant bonding (MIB) in patients who delivered vaginally and who delivered with C/S using Maternal Attachment Inventory (MAI), Edinburgh Postnatal Depression Scale (EPDS) and Postpartum Specific Anxiety Scale (PSAS) in the Turkish population. Secondary aim was to evaluate the correlations between the MAI, EPDS and PSAS scores and their association with sociodemographic data.Methods: A total of 200 patients were divided into two groups. 100 women who delivered vaginally were included in the vaginal delivery (NVD) group and 100 who delivered with cesarean section were included in the C/S group. The demographic data of the subjects including age, gravidity, and parity, were recorded and a detailed anamnesis was taken at the day of hospitalization for delivery. In addition, newborns’ genders were taken into evaluation. All patients were asked to complete MAI, EPDS and PSAS at the 3rd month postpartum control.Results: PSAS score in the NVD group was calculated to be 68.9 ± 9.0, which was significantly higher than C/S group 65.0 ± 9.6 (p = 0.005). However, MAI and EPDS scores in both groups were calculated to be similar (p = 0.833 and p = 0.260, respectively). A significant negative correlation was observed between age and MAI (r = -0.180, p = 0.011) and between number of children and MAI (r = -0.140, p = 0.048).Conclusions: According to the results of this study which was conducted using a Turkish cohort maternal age at delivery and number of children at home are the factors which had an effect on MIB. On the other hand, mode of delivery did not play a role on MIB among this study population. However, multicenter studies with larger number of subjects are needed to make a general conclusion regarding the Turkish population.